Implementasi Augmented Reality Sebagai Media Edukasi dan Promosi Aceh Tenggara Menggunakan Metode Markerless - Barus, Ilfan Daniel; Usman, Ari; Dharmawati, Dharmawati (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2025)
The growing development of technology has a positive impact on everyone's activities. Like being able to access tons of facilities and information using only a smartphone and internet connection. However, technology also brings a bad impact as well, easily accessing various information on the internet such as western pop content, K-pop and the like causes a shift in the value of love for local traditional culture of the Indonesian people, in this study specifically Southeast Aceh. Collaboration between technology and traditional culture needs to be done so that all kinds of cultural heritage can still be accessed using smartphones anywhere and anytime. This research aims to implement AR technology as an educational and promotional media using the markerless method. Qualitative research methods with a case study approach are used to analyze data obtained through questionnaire statements. There were 23 questionnaire respondents who stated that 65.2% stated that this application helped recognize the Southeast Aceh region and 47.8% of respondents stated that the experience when using the application was very good and 47.8% of respondents stated that the experience when using the application was good. The conclusion of this research is the formation of an android-based augmented reality application using the markerless method that produces innovative, educational solutions, allowing interactive and realistic experiences in increasing understanding of Southeast Aceh culture and expanding the range of information and enriching user experience through multimedia content such as 3D objects in a real environment without the need for markers.